2018
DOI: 10.1016/j.bbadis.2017.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cardiac pathology in diabetes – Experimental insights

Abstract: Diabetic cardiomyopathy is a distinct pathology independent of co-morbidities such as coronary artery disease and hypertension. Diminished glucose uptake due to impaired insulin signaling and decreased expression of glucose transporters is associated with a shift towards increased reliance on fatty acid oxidation and reduced cardiac efficiency in diabetic hearts. The cardiac metabolic profile in diabetes is influenced by disturbances in circulating glucose, insulin and fatty acids, and alterations in cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 183 publications
5
80
0
4
Order By: Relevance
“…Cardiovascular complications, including diabetic cardiomyopathy (DCM), represent the leading causes of morbidity and mortality in diabetic patients [1,2]. DCM is mainly characterized by myocardial fibrosis, chronic inflammation, and structural and functional cardiac changes caused by long-term glucose abnormalities [3][4][5]. In particular, cardiac fibrosis is often accompanied by increased pro-fibrotic factors such as transforming growth factor (TGF)-β, proliferation and dysfunction of cardiac fibroblasts, increased deposition, and decreased degradation of extracellular matrix proteins (ECM) such as collagen, leading to increased ventricular wall stiffness, abnormal cardiac filling, and diastolic and contractile cardiac dysfunction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular complications, including diabetic cardiomyopathy (DCM), represent the leading causes of morbidity and mortality in diabetic patients [1,2]. DCM is mainly characterized by myocardial fibrosis, chronic inflammation, and structural and functional cardiac changes caused by long-term glucose abnormalities [3][4][5]. In particular, cardiac fibrosis is often accompanied by increased pro-fibrotic factors such as transforming growth factor (TGF)-β, proliferation and dysfunction of cardiac fibroblasts, increased deposition, and decreased degradation of extracellular matrix proteins (ECM) such as collagen, leading to increased ventricular wall stiffness, abnormal cardiac filling, and diastolic and contractile cardiac dysfunction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…K ATP plays a key protective role in the heart through various signaling pathways. Speci cally, genetic manipulation of cardiomyocyte insulin signaling intermediates has demonstrated that partial cardiac function rescue was achieved by upregulation of the insulin signaling pathway in diabetic hearts [37]. Similarly, a previous study has reported that the cardioprotective effect of K ATP occurs at least partially by regulating the AKT-Foxo1 signaling pathway, which in turn in uences the expression of PGC-1α and its downstream target genes [38].…”
Section: Discussionmentioning
confidence: 95%
“…The hexosamine biosynthetic pathway, protein kinase C pathway, advanced glycation end-products pathway, and polyol flux pathway secondary to an increase of hyperglycemia can all produce contractile dysfunction, which can lead to systolic HF in a patient with DCM. 16,17 Can Diagnosis be Improved?…”
Section: Does Diabetic Cardiomyopathy Have a Simple Physiopathology?mentioning
confidence: 99%